Penerapan Strategi Pembelajaran Menyimak Berbasis Media Digital: Upaya Meningkatkan Konsentrasi dan Keterlibatan Siswa Kelas V SD Negeri 1 Magelang - Kamila, Nisfa Laila; Chadiatno, Abdillah Ramdani; Sari, Anggun Kharisma; Melani, Rara Puspa; Hawaingrum, Tri Sinta; Irvan, Moh. Farizqo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the effectiveness of implementing a digital media-based listening learning strategy in improving the concentration and engagement of fifth-grade students at SD Negeri 1 Magelung. The background of the study stems from the low concentration and participation levels of students during conventional listening learning. This research used a descriptive qualitative approach with data collected through interviews, questionnaires, and classroom observations. The findings indicate that digital media such as videos, audio, LCDs, and applications like Canva positively influenced student attention, enhanced memory retention, and encouraged active participation in classroom discussions. Despite challenges such as potential misuse of smartphones and extended preparation time, the teacher successfully overcame them through appropriate strategies. These results confirm that digital media-based listening strategies are effective in creating an interactive, enjoyable, and digitally relevant learning environment